Four terpene synthases contribute to the generation of chemotypes in tea tree (Melaleuca alternifolia) - Amanda Padovan; Andras Keszei; Yasmin Hassan; Sandra T. Krause; Tobias G. Köllner; Jörg Degenhardt; Jonathan Gershenzon; Carsten Külheim; William J. Foley (BMC Plant Biology, 2017)
Abstract Background Terpene rich leaves are a characteristic of Myrtaceae. There is significant qualitative variation in the terpene profile of plants within a single species, which is observable as “chemotypes”. Understanding the molecular basis of chemotypic variation will help explain how such variation is maintained in natural populations as well as allowing focussed breeding for those terpenes sought by industry. The leaves of the medicinal tea tree, Melaleuca alternifolia, are used to produce terpinen-4-ol rich tea tree oil, but there are six naturally occurring chemotypes; three cardinal chemotypes (dominated by terpinen-4-ol, terpinolene and 1,8-cineole, respectively) and three intermediates. It has been predicted that three distinct terpene synthases could be responsible for the maintenance of chemotypic variation in this species. Results We isolated and characterised the most abundant terpene synthases (TPSs) from the three cardinal chemotypes of M. alternifolia. Functional characterisation of these enzymes shows that they produce the dominant compounds in the foliar terpene profile of all six chemotypes. Using RNA-Seq, we investigated the expression of these and 24 additional putative terpene synthases in young leaves of all six chemotypes of M. alternifolia. Conclusions Despite contributing to the variation patterns observed, variation in gene expression of the three TPS genes is not enough to explain all variation for the maintenance of chemotypes. Other candidate terpene synthases as well as other levels of regulation must also be involved. The results of this study provide novel insights into the complexity of terpene biosynthesis in natural populations of a non-model organism.